2016
DOI: 10.1109/tbme.2015.2467312
|View full text |Cite
|
Sign up to set email alerts
|

EEG Source Imaging Enhances the Decoding of Complex Right-Hand Motor Imagery Tasks

Abstract: Goal Sensorimotor-based brain-computer interfaces (BCIs) have achieved successful control of real and virtual devices in up to three dimensions; however, the traditional sensor-based paradigm limits the intuitive use of these systems. Many control signals for state-of-the-art BCIs involve imagining the movement of body parts that have little to do with the output command, revealing a cognitive disconnection between the user’s intent and the action of the end effector. Therefore, there is a need to develop tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
202
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(210 citation statements)
references
References 64 publications
4
202
0
4
Order By: Relevance
“…An electroencephalogram (EEG) can record sensorimotor rhythm activities (Yuan and He, 2014;Edelman et al, 2016) and show clear functional specificity during planned, actual, or imagined movements. These imagined movements of extremities cause specific EEG patterns, such as a desynchronization of mu and central beta rhythms at the contralateral sensorimotor area (Pfurtscheller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An electroencephalogram (EEG) can record sensorimotor rhythm activities (Yuan and He, 2014;Edelman et al, 2016) and show clear functional specificity during planned, actual, or imagined movements. These imagined movements of extremities cause specific EEG patterns, such as a desynchronization of mu and central beta rhythms at the contralateral sensorimotor area (Pfurtscheller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The source analysis methods, which are used to analysis brain signals in source spaces and translate noninvasively recorded scalp signals into physical regions, are potential methods for us to explore the inner workings of the brain [11]. Taking advantage of source analysis methods such as equivalent dipole model and cortical imaging technique are thought to be potential methods for classifying MI tasks in BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…Pascual-Marqui came up with another method named standard low-resolution electromagnetic tomography (sLORETA) [13] with zero location error. Brad Edelman [11] used weighted minimum norm estimate (WMNE) to search out the optimal source distribution; the results showed that four-class classification of right hand tasks by using EEG source imaging approach were able to improve nearly 10% compared with traditional technology. Xu et al proposed NEtwork based SOurce Imaging (NESOI) method [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the macroscopic EEG signal is generally believed to originate from well-localized gray matter sources [8,9], and therefore makes full 3D spatial reconstruction of the dipole source distribution a valuable imaging modality. The source reconstruction process has been shown to reduce non-brain artifact signal components [10]; it allows incorporation of spatial a priori information from functional activation databases [11]; and it generally leads to improved interpretability [12,13] by reducing the blurring effects of volume conduction.…”
Section: Introductionmentioning
confidence: 99%